Oxidation of unsaturated aldehydes by peracetic acid - Pikh, Zoryan; Nebesnyi, Roman; Ivasiv, Volodymyr; Pich, Andrij; Vynnytska, Sofia (Publishing House of Lviv Polytechnic National University, 2016)
The paper is dedicated to studies of kinetic regularities of oxidation of unsaturated aldehydes by organic peracids. The routes of products formation were considered, kinetic model of the oxidation reaction was designed and reaction activation parameters were calculated based on experimental data. New data on reactivity of aldehydes with various structures in the reaction with peracids were obtained. Стаття присвячена дослідженню кінетичних закономірностей реакції окиснення ненасичених альдегідів органічними перкислотами. На основі експериментальних даних запропоновано шляхи утворення продуктів, розроблено кінетичну модель реакції окиснення та розраховано активаційні параметри реакції. Наведено нові дані про реакційну здатність альдегідів різної будови в реакції з перкислотами.
Окиснення ненасичених альдегідів органічними перкислотами
Keywords: oxidation with peracids; unsaturated aldehydes; mechanism of the reaction; kinetic and activation parameters; окиснення перкислотами; ненасичені альдегіди; механізм реакції; кінетичні та активаційні параметри реакції